Clinical Profile of Gun Shot Abdominal Injuries and A Comparative Evaluation with Experimental Gun Shot Firings (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
Of late, incidence of gunshot injuries are exhibiting a quantum leap owing to easy  availability of firearms. Abdominal gunshot ranged from minor superficial pellet injuries  to devastating soft tissues and visceral injuries.  The study included 30 cases of abdominal gunshot and other associated injuries admitted  to surgery wards of SRN Hospital. Younger age group (21-30 yrs) was more commonly  involved 7(23.33%). M: F ratio was 6.5:1. The rural-urban ratio was 1.5:1. Most cases  20(66.67%) were due to assault. 24(80%) received bullet injuries and 6(20%) shotgun  injuries. In 19(63.33%) cases 0.315 mm bullet was responsible, of these 15(50%) were  due to country made ‘Katta’. 0.32 mm bullet was used only in 4(13.33%) cases. 28 were  operated upon and in 2 cases of pellet injury (Type-I) conservative management was  done. 22 patients of bullet and 5 pellet injuries were recovered and 3 cases expired.
Keywords: small bowel; devastating soft